Advanced image restoration techniques - Mok, Chi Kin. (2010)
The purpose of this report is to provide a summary of the investigation and research into the problem of restoring blurred and noisy images. The Matlab™ for Microsoft Windows™ is used in this project to implement different algorithms. In real life, pictures taken by a camera may be blurred due to the motion of either the camera or the target, or the defocusing of the camera. These blurs can be modeled as point spread functions (PSF). The knowledge of the PSF is important as it is required in the restoration processes. When the PSF is known, image restoration methods like Inverse Filtering and Wiener Filtering can be used to restore the pictures.